No Tangible Effects of Field-Grown Cisgenic Potatoes on Soil Microbial Communities - Krause, Sascha M. B.; Näther, Astrid; Ortiz Cortes, Vilma; Mullins, Ewen; Kessel, Geert J. T.; Lotz, Lambertus A. P.; Tebbe, Christoph C. (Frontiers in Bioengineering and Biotechnology, 2020)
DNA modification techniques are increasingly applied to improve the agronomic performance of crops worldwide. Before cultivation and marketing, the environmental risks of such modified varieties must be assessed. This includes an understanding of their effects on soil microorganisms and associated ecosystem services. This study analyzed the impact of a cisgenic modification of the potato variety Desirée to enhance resistance against the late blight causing fungus Phytophthora infestans (Oomycetes) on the abundance and diversity of rhizosphere inhabiting microbial communities. Two experimental field sites in Ireland and the Netherlands were selected, and for two subsequent years the cisgenic version of Desirée was compared in the presence and absence of fungicides to its non-engineered late blight sensitive counterpart and a conventionally bred late-blight resistant variety. At flowering stage, total DNA was extracted from the potato rhizosphere and subjected to PCR for quantifying and sequencing bacterial 16S rRNA genes, fungal ITS sequences, and nir genes encoding for bacterial nitrite reductases. Both bacterial and fungal communities responded to field conditions, potato varieties, year of cultivation, and, bacteria sporadically also to fungicides treatments. At the Dutch site, without annual replication, fungicides stimulated nirK abundance for all potatoes, but with significance only for cisgenic Desirée. In all other cases neither the abundance nor the diversity of any microbial marker differed between both Desirée versions. Overall the study demonstrates environmental variation but also similar patterns of soil microbial diversity in potato rhizospheres and indicates that the cisgenic modification had no tangible impact on soil microbial communities.